Effect of Elevated CO2 on Biomass Production, Photosynthesis and Carbon Sequestration of Cenchrus ciliaris and Stylosanthes hamata under Intercropping System - Bhatt, R.K.; Baig, M.J.; Tiwari, H.S.; Dubey, Jyoti; Yadava, R.B. (Indian Journal of Agroforestry, 2020)
Effect of elevated CO2 (600±50 ppm) on biomass production, assimilatory functions and chlorophyll accumulation was studied in Cenchrus ciliaris + Stylosanthes hamata intercropping systems in open top chambers (OTCs) and in open field conditions. C. ciliaris + S. hamata produced 106% and 141% higher fresh and dry biomass respectively under elevated CO2 (600±50 ppm). Rates of photosynthesis and stomatal conductance increased in both the crop species in intercropping systems under elevated CO2 (600±50 ppm) over open grown crops. Due to increase in the rate of photosynthesis and leaf area index the canopy photosynthesis of these crop species increased significantly under elevated CO2 over the open grown crops. The accumulation of chlorophyll a and b was also higher in the leaves of all crop species as grown in intercropping system in OTC with elevated CO2 (600±50 ppm). The increased chlorophyll content, leaf area index and canopy photosynthesis led to higher growth and biomass production in these crop species under elevated CO2. The total carbon sequestration during the three years by the crops (including soil C) was 19.73 Mg C/ha under elevated CO2 (600±50 ppm). Therefore, this intercropping system indicated its potential as a sink for the increasing level of CO2 in the atmosphere in the semi-arid tropics.